Busayra excavations by Crystal-M. Bennett, 1971-1980 - Bienkowski, Piotr (Council for British Research in the Levant, 2002)
This volume is the long-awaited final report on the late Crystal Bennett's 1971-1980 excavations at Busayra, the major city of the Iron Age kingdom of Edom in southern Jordan. Dr. Bienkowski and specialist contributors describe and illustrate the architecture, stratigraphy, pottery and other finds of this impressive fortified administrative and religious center. The concluding chapter puts the nature and role of Busayra into its proper ancient context in the light of current research on tribal kingdoms. Library of Congress subject headings for this publication: Busayra Site (Busayra, Jordan) Excavations (Archaeology) -- Jordan -- Busayra. Iron age -- Jordan -- Busayra.